Centro Administrativo de Uberlândia: análise das transformações espaciais, da ideia inicial à obra executada - Garcias, Elcio de Oliveira (2019)
This research starts from the observation about a recurring theme in architecture that is the difference between the discourse, the project as an idea, and the results achieved in practice with that same idea or concept. That said, the objective was to study a work in order to understand the transformations that it went through from its initial conception to its post-inauguration period. For this purpose, the Centro Administrativo de Uberlândia was chosen as an object, a set of buildings designed from the project presented in a competition held in 1990, whose winning team included Acácio Gil Borsoi, Janete Costa, Milton Leite, Marco Antônio Borsoi, and Rosa Maria Chagas Aroucha. Its choice was due to the fact that it is a work in which the project documentation is available at various times, from the preliminary study to the work performed, in addition to its importance within the framework of Brazilian architecture. The methodology covered a survey of information about the Centro Administrativo in order to understand the changes it underwent. With this data, a project analysis was developed, which was later combined with certain post-occupancy evaluation (POE) tools that would contribute to a better understanding of how the analyzed aspects behaved in the building as it is today. For the project analysis, the methodology proposed by Leupen et al in the book Project and Analysis was chosen because it is more comprehensive, especially with regard to the spatial context in which the work is inserted. With regard to POE tools, walkthrough, behavioral maps and bioclimatic comfort assessments were chosen. Based on the results obtained in the research, it is possible to list positive and negative aspects of the project and understand the origin of certain problems, which mostly refer to the preliminary study and executive project phase, thus answering the initial question raised by this research.